Analisis Pengaruh Kesadaran Merek, Persepsi Kualitas, Dan Loyalitas Merek Terhadap Kepuasan Konsumen Pada ProdukPrivate Label Indomaret - Pratama, Miken Selly; , Dr. Edy Purwo Saputro, S.E., M.Si (2017)
The aim of this research to analyze influence of brand areness (X1),perception quality (X2), and brand loyalty (X3) of customer satisfaction (Y) on Indomaret private label product in Universitas Muhammadiyah Surakarta area. Research population is all of Economy and Bussiness Department udents in UMS. The technique sampling in this research is purposive sampling by take 100 respondences based on criteria. This research uses classic assumption test and double linear regression (t test, F and R2). Based on the result are found some finding, the first is brand awareness has positive influence but not significant at coustomer satisfaction in indomaret private label product. Second, quality perception has positive influence and significant at consumen isfaction in customer satisfaction of indomaret private label product. Third, brand loyalty has positive influence and significant at customer satisfaction in indomaret private label product. The last, brand awareness, quality perception, brand loyalty are correct model to explain customer satisfaction in indomaret private label product. This research gives suggestion to company to choose correct strategy to increase customer satisfaction.